A highly active selenized nickel–iron electrode with layered double hydroxide for electrocatalytic water splitting in saline electrolyte. (March 2021) - Hung, W.-H.; Xue, B.-Y.; Lin, T.-M.; Lu, S.-Y.; Tsao, I.-Y.
Abstract: The oxygen evolution reaction (OER) is the half reaction in the overall reaction of electrocatalytic water splitting, and it involves four electron transfers. The aforementioned electron requirement implies that the OER requires more energy than the HER, thus limiting the overall water splitting efficiency. Here, we propose a novel anode catalyst by using an advanced composite material of selenized nickel–iron electrodes together with NiFe_LDH. An analysis of the water splitting performance was carried out in different concentrations of a seawater-like electrolyte, which, in terms of corrosion reactions, is a relatively harsher environment than that found in natural seawater. In this study, we discovered that a Se_NiFe foam electrode with an LDH layer exhibited extraordinary stability and activity in an aqueous sea-like solution, demonstrating an improved overpotential from the original 1.62 V–1.43 V in a seawater electrolyte mixture. Furthermore, the Tafel slope significantly decreased from 115.1 mV dec −1 to 26.3 mV dec −1 . Notably, the lifespan of this novel electrode was extended from 80 h to 250 h. The mechanism of improved stability and corrosion resistance is also investigated in this study. Graphical abstract: Image 1 Highlights: Oxygen can be selectively and stably generated in seawater-like solution with cheap electrode materials and electrode architecture. Selenized nickel–iron electrodes with the selenide layer possessed good conductivity and corrosion resistance. The NiFe–LDH layer on the electrodes surface, which can effectively reduce overpotential and improve corrosion. This study successfully demonstrated the lifespan of this novel electrode was extended upto 250 h for industrial application.